Validation of the distress thermometer for caregivers of children and adolescents with schizophrenia. (8th January 2020) - Bai, Xiaoling; Wang, Anni; Cross, Wendy; Lam, Louisa; Plummer, Virginia; Guan, Ziyao; Sun, Mei; Tang, Siyuan
Abstract: Aim: To develop and psychometrically test the distress thermometer for caregivers (DT‐C) and document the distress level in primary caregivers of children and adolescents diagnosed with schizophrenia. Design: A validation diagnostic accuracy study and descriptive cross‐sectional survey. Methods: DT‐C was adopted based on Harverman's distress thermometer for parents. The cut‐off score was detected by using receiver operating characteristic analysis with the Depression Anxiety Stress Scale‐21 as a reference standard in a sample of 324 caregivers of children and adolescents diagnosed with schizophrenia in China collected between Jan 2017 and Feb 2018. Results: One‐item DT of DT‐C indicated a good retest reliability ( r  = 0.86) and one‐item DT and the Problem List (PL) indicated good convergent validity ( r  = 0.67–0.88). Overall and individual PL domains showed good internal consistency ( KR 20 values ranged from 0.70–0.90). Setting seven as the cut‐off score, the values of sensitivity (0.72–0.81), specificity (0.86–0.90), Youden's index (0.61–0.70), positive predictive value (0.67–0.74), and negative predictive value (0.84–0.92) were most satisfactory and area under curve values showed significantly excellent discrimination (0.88–0.90). The average DT score for the 324 participants was 6.34 ( SD 2.49), with 46.9% of the participants above the cut‐off. Caregivers above the cut‐off score faced significant multiple problems in practical, family/social, cognitive, emotional, and parenting domains. Conclusion: The DT‐C, with six domains containing 35 items in Problem List and with the cut‐off score at seven, can be a rapid screening tool to measure distress in these caregivers. The level of distress in caregivers was relatively high. Psychoeducation on specific needs and a solid mutual support network are recommended for mitigating caregivers' distress. Impact: This study adapted a reliable DT‐C to measure distress of caregivers, which has the potential to be introduced to caregivers of other types of child and adolescent mental disorders in research, assessments and care planning for health professionals. Abstract : 目的: 开发和护理者的痛苦温度计(DT‐C), 从心理测量学上进行测试, 并记录被诊断为精神分裂症的儿童和青少年的主要护理者的痛苦程度。 设计: 验证诊断准确性研究和描述性横断面调查。 方法: 采用的痛苦温度计是在Harverman的父母痛苦温度计的基础上设计的。采用焦虑抑郁压力量表‐21进行接受者操作特征分析, 检测出临界值, 作为中国2017年1月至2018年2月之间诊断出儿童精神分裂症儿童和青少年324名护理者的参照标准。 结果: 痛苦温度计中的一项DT表示良好的重测信度( r =0.86), 一项DT和问题表(PL)表示良好的收敛效度( r =0.67‐0.88)。整体和个别问题表域显示出良好的内部一致性( KR 20 值范围为0.70‐0.90)。以7为临界值时, 敏感性(0.72‐0.81)、特异性(0.86‐0.90)、尤登指数(0.61‐0.70)、阳性预测值(0.67‐0.74)和阴性预测值(0.84‐0.92)最为满意, 曲线下面积值显示出显著的优异区分性(0.88‐0.90)。324名参与者的平均DT得分为6.34(SD为2.49), 46.9%的参与者高于临界值。高于临界值的护理者在工作、家庭/社会、认知、情感和养育方面面临着重大的多重问题。 结论: 痛苦温度计有6个领域, 包含问题列表中的35个项目, 临界值为7, 可以作为一个快速筛查工具来测量这些护理者的痛苦程度。护理者的痛苦程度相对较高。建议针对特定需要进行心理教育, 并建立稳固的互助网络, 以减轻护理者的痛苦。 影响: 本研究采用了可靠的痛苦温度计来测量护理者的痛苦程度, 有可能被引入到其他类型儿童和青少年精神障碍的护理者的研究、评估和保健专业人员的护理计划中。